Double Skin Façade: A Green Building Strategy Approach Towards Low Carbon Architecture - Dewi, Cynthia Permata; Ikaputra, Ikaputra (Sinektika: Jurnal Arsitektur, 2025)
The emergence of global warming due to the increase in the amount of carbon emissions and greenhouse gas emissions is caused by one of the activities of the construction industry sector. Green building is one of the solutions that can help reduce energy consumption in buildings and carbon emissions in the building life cycle. Double Skin Façade (DSF) is one of the green building strategies that can be applied to new and existing buildings. This study aims to determine the type of DSF used in the field and how DSF can affect the energy consumption of buildings. This research uses a narrative review method that focuses on the application of the DSF strategy, how the mechanism works on the type of DSF used. The results show that the use of DSF is able to reduce HVAC energy loads in buildings in various types of climates. Stack effect as a key capability of DSF is able to create airflow in the air gap so as to stimulate air movement which in turn can reduce the use of HVAC in buildings. This shows that the DSF strategy is one of the green building strategies that has great potential to be developed in the future.